Crowd‐Funded Journalism. Issue 2 (11th December 2013) - Jian, Lian; Usher, Nikki
Abstract Crowd‐funded journalism is a novel business model in which journalists rely on micropayments from ordinary people to finance their reporting. Based on analyses of the database of Spot.us, a pioneering crowd‐funded journalism website, we examine the impact of crowd‐funded journalism on the news produced. We apply a uses and gratifications approach to study consumers' choices when they donate to crowd‐funded journalism and find that consumers are more likely to donate to stories that provide them with practical guidance for daily living (e.g., stories about public health or local city infrastructure), as opposed to stories from which they gain a general awareness of the world (e.g., cultural diversity, or government and politics). We discuss the implications for the future of news.